2018
DOI: 10.7759/cureus.2482
|View full text |Cite
|
Sign up to set email alerts
|

Infective Endocarditis Associated with Atrial Septal Defect in an Intravenous Drug Abuser: A Case Report

Abstract: Atrial septal defect (ASD) is a common congenital abnormality, which accounts for 20-40% of all the adult patients with congenital heart diseases. Due to the slow velocity of shunt flow, ASD has a negligible risk for infective endocarditis (IE). However, intravenous drug abuse (IVDA) is a potential cause for IE. IE remains a diagnostic and therapeutic challenge. Our case report demonstrates the atypical presentation of IE in an ASD patient. The diagnosis was made on the basis of modified Duke criteria, and blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Moreover, it has recently been shown that there is clear delay in establishing IE diagnosis amongst CHD patients in Central and South-Eastern European countries [11]. However, relative to other congenital diseases, the association between ASD and IE is very rare, at only around 0.4% [12,13].…”
Section: Current Reports and Actual Evidencementioning
confidence: 99%
“…Moreover, it has recently been shown that there is clear delay in establishing IE diagnosis amongst CHD patients in Central and South-Eastern European countries [11]. However, relative to other congenital diseases, the association between ASD and IE is very rare, at only around 0.4% [12,13].…”
Section: Current Reports and Actual Evidencementioning
confidence: 99%